New Perspectives on Picture Books - Lisa Ciecierski; James Nageldinger; William P. Bintz; Sara D. Moore (Athens Institute for Education and Research, 2017)
The use of picture books has been illuminated as a potential to address important topics such as STEM, fluency, and social justice. Unique genres such as hybrid texts and wordless picture books are also worth considering for instruction. This article explores new perspectives on using picture books. Potentials for using wordless picture books beyond the early grades to support literacy across the curriculum are shared first. Next, we discuss how some picture books lend themselves to the engineering design cycle and can be used as an organizing idea for instruction which focuses on integrating the STEM disciplines. To continue, the prospect of utilizing picture books to strengthen reading fluency while engaging students in rich content area material is discussed. The potentials for using banned and challenged picture books to teach social justice is discussed next. We conclude by presenting practical strategies, picture books to consider for each of the areas, and lessons learned.